Scottish Confidential Inquiry into Asthma Deaths (SCIAD), 1994–6. Issue 11 (1st November 1999) - Bucknall, C E; Slack, R; Godley, C C; Mackay, T W; Wright, S C
Abstract : BACKGROUND: There have been important changes in the organisation of care for patients with asthma since asthma deaths were studied in the 1980s by the British Thoracic Association (BTA), with greater emphasis on long term control of symptoms and the use of preventive therapy. Recent trends in routine statistics show a decline in population death rates. METHODS: A confidential review was undertaken of general practice and hospital records and interviews with general practitioners of patients dying in mainland Scotland between January 1994 and December 1996 with a principal diagnosis of asthma recorded by the Registrar General's Office. Panel assessment of the cause of death was carried out and a number of possible adverse factors were identified. The data from the 15–64 year age group were compared with similar data from the earlier study by the BTA. RESULTS: Over the three year period 95 deaths of 235 studied (40%) were confirmed as being due to asthma. Taking account of different methods of case ascertainment used in the BTA and this study, a fall in the calculated rate of "deaths assessed as due to asthma" was found from 2.51 (95% CI 2.34 to 2.68) per 100 000 population in 1979 to 1.26 (95% CI 1.19 to 1.33) per 100 000 population in 1994–6. Fewer individual adverse factors were identified in clinical management, with appropriate routine management in 59% and management of the final attack satisfactory in 71%. Patient factors such as poor compliance, lack of peak expiratory flow (PEF) measurements, and overuse of reliever medication without inhaled corticosteroids, and psychosocial problems, notably depression, were confirmed as important contributing factors. Four of five patients under 16 years of age who died were found to have problems with routine management. CONCLUSIONS: This population based study documents important improvements in the standard of asthma care as well as a significant decline in the rate of deaths due to asthma over a period during which the organisation of care has changed and the chronic nature of the disease has been acknowledged. Strategies which might have a further impact include the greater use of PEF recordings, particularly during acute attacks, to document recovery, prescription monitoring of the underuse of inhaled corticosteroids, consideration of the use of combined preparations where persistent overuse of bronchodilators is occurring, and increased input for young patients whose routine management is proving difficult.